Elections and democracy in Central America - Booth, John A., 1946-; Seligson, Mitchell A. (University of North Carolina Press, 1989)
Introduction -- Elections and democracy and in Central America : A framework for analysis / John A. Booth -- Can democracy survive the democrats?: from transition to consolidation in Honduras / Mark B. Roseberg -- El Salvador: Recent elections in historical perspective / José Z. García -- The Guatemalan election of 1985: prospects for democracy / Robert H. Trudeau -Elections and transitions: the Guatemalan and Nicaraguan cases / Sussane Jonas -- Ordinary elections in extraordinary times . the political economy of voting in Costa Rica / Mitchell A. Seligson and Miguel Gómez B. -- Democracy and elections in Central America: autumn of the oligarchs? / John A. Peeler.